STUDI PENDAPATAN NELAYAN BERDASARKAN JENIS ALAT TANGKAP NELAYAN DI KECAMATAN SIMBORO DAN KEPULAUAN KABUPATEN MAMUJU - Hamjan, Dewi Febriani; Nurliana, Nurliana; Kamaruddin, Kamaruddin (Universitas Muhammadiyah Gresik, 2025)
The income of fishermen from their livelihood as fish catchers is still relatively low, so they are often in unfavorable economic conditions. This can be caused by a lack of knowledge of fishermen or fishermen not using the right fishing gear. So this study aims to analyze the income earned by fishermen based on the fishing gear used by fishermen. This research uses a survey method, which is an approach that takes samples from a population using a questionnaire as the main instrument for data collection. Respondents who were sampled were capture fishermen in Simboro and Kepulauan sub-districts. The determination of the number of samples was based on the level of homogeneity of the population. The research population includes fishermen who use fishing rods, sero, and gill nets, totaling 33 people. The purposive sampling technique is a sampling technique that determines certain criteria. This research was conducted from August to December 2024 in Simboro and Islands Sub-districts, Mamuju Regency. The results showed that fishermen who operated fishing gear were optimal and included in the medium welfare category. The results of the analysis show that the average income per year of fishermen using fishing gear reaches Rp. 33,056,667, with an average income per month of Rp. 2,754,72. However, fishermen who use sero and gillnet gear are still in the low category, which indicates the urgency to improve the economic welfare of fishermen in the region through all relevant stakeholders.